The Function of the Hypothalamic–Pituitary–Adrenal Axis During Experimental Autoimmune Encephalomyelitis: Involvement of Oxidative Stress Mediators - Trifunovic, Svetlana; Stevanovic, Ivana; Milosevic, Ana; Ristic, Natasa; Janjic, Marija; Bjelobaba, Ivana; Savic, Danijela; Bozic, Iva; Jakovljevic, Marija; Tesovic, Katarina; Laketa, Danijela; Lavrnja, Irena (Frontiers in Neuroscience, 2021)
Multiple sclerosis (MS) is an inflammatory, demyelinating disease with an unknown origin. Previous studies showed involvement of the hypothalamic-pituitary-adrenal (HPA) axis to susceptibility to autoimmune diseases, including MS and its best-characterized animal model, experimental autoimmune encephalomyelitis (EAE). During MS/EAE innate immune cells are activated and release cytokines and other inflammatory mediators, leading to a vicious cycle of inflammation. In response to inflammation, the activated HPA axis modulates immune responses via glucocorticoid activity. Because, the mechanisms involving oxidative stress to the HPA axis are relatively unrevealed, in this study we investigate the inflammatory and oxidative stress status of HPA during EAE. Our results reveal an upregulation of Pomc gene expression, followed by POMC and ACTH protein increase at peak of the EAE in the pituitary. Also, prostaglandins are well-known contributors of HPA activation, which increases during EAE at the periphery. The up-regulated Tnf expression in the pituitary during the peak of EAE occurred. This leads to the activation of oxidative pathways, followed by upregulation of inducible NO synthase expression. The reactive oxidant/nitrosative species (ROS/RNS), such as superoxide anion and NO increase their levels at onset and peak of disease in the pituitary and adrenal glands, returning to control levels at the end of EAE. The corticotrophs in the pituitary increased in number and volume at the peak of EAE that coincides with high lipid peroxidation levels. The expression of MC2R in the adrenal glands increases at the peak of EAE, where strong induction of super-oxide anion and malondialdehyde (MDA), reduced total glutathione (GSH) content and catalase activity occurred at peak and end of EAE compared to controls. The results obtained from this study may serve to understand the mechanisms and possible pharmacological modulation in MS and they demonstrate an effect of oxidative stress exposure in the HPA activation during the course of the EAE.